2022
DOI: 10.2967/jnumed.122.264516
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Strain from Myocardial Perfusion PET Imaging: Method Development and Comparison to 2-Dimensional Echocardiography

Abstract: This study aimed to develop a measure of longitudinal, radial, and circumferential myocardial strain at rest and regadenoson during pharmacologic stress using 82 Rb PET electrocardiography-gated myocardial perfusion imaging (MPI). Methods: We retrospectively identified 80 patients who underwent rest and regadenoson-stress CT attenuationcorrected 82 Rb PET and had a standard resting transthoracic echocardiogram (TTE) with global longitudinal strain (GLS) analysis within 3 mo. A method was developed to compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Aside from cardiac MRI, there is limited data to assess myocardial strain derived from other non-invasive cardiac imaging modalities. Our group recently developed a method to measure left ventricular strain from gated myocardial perfusion images and showed that it correlates well with TTE-derived strain [ 5 ]. Apical strain index (ASI), apex-to-base ratio (ABR), and ejection fraction to global strain are three parameters that have been used to distinguish cardiac amyloidosis from other causes of left ventricular hypertrophy (LVH) [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from cardiac MRI, there is limited data to assess myocardial strain derived from other non-invasive cardiac imaging modalities. Our group recently developed a method to measure left ventricular strain from gated myocardial perfusion images and showed that it correlates well with TTE-derived strain [ 5 ]. Apical strain index (ASI), apex-to-base ratio (ABR), and ejection fraction to global strain are three parameters that have been used to distinguish cardiac amyloidosis from other causes of left ventricular hypertrophy (LVH) [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%